CHANGING PROFILE OF ENTERIC FEVER IN CHILDREN - Burki, Mumtaz Khan; Wazir, Mehr Dil Khan; Shah, Humayun (Journal of Ayub Medical College Abbottabad, 1995)
A total of 300 cases of PUO (Pyrexia of Unknown Origin) were admitted to the Paediatrics Unit of Women and Children Hospital, Abbottabad during one year (June 1994 - May, 1995). They were examined for their detailed clinical profile. About 2/3rd of them had fever as their presenting symptom. Other associated predominant features were dizziness-51 (30%), anorexia-48 (28%), loose motions-47 (27.6%), cough-38 (22.4%}), headache-25 (14.7%), coated tongue-21 2(12.4%.), & jaundice-5 (2.9%). 80%, patients were admitted when complications had developed, such as gastroenteritis-68 (40%), enteric encephalopathy- 65 (38.2%), drug toxicity-30 (17.6%), peritonitis-25 (14.7%), cholecystitis-18 (10.6%), myocarditis-6 (3.5%), and ataxia-2 (1.2%). In the first 9 months, response to chloramphenicol was very good but this changed to resistance and in the last 3 months most of the cases were resistant to chloramphenicol treatment.